2019
DOI: 10.1093/ije/dyz216
|View full text |Cite
|
Sign up to set email alerts
|

Solid fuels for cooking and tobacco use and risk of major chronic liver disease mortality: a prospective cohort study of 0.5 million Chinese adults

Abstract: Background Harmful substances in solid fuel and tobacco smoke are believed to enter the bloodstream via inhalation and to be metabolized in the liver, leading to chronic liver damage. However, little is known about the independent and joint effects of solid fuel use and smoking on risks of chronic liver disease (CLD) mortality. Methods During 2004–08, ∼0.5 million adults aged 30–79 years were recruited from 10 areas across Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 39 publications
1
31
0
Order By: Relevance
“…Percentages and means of selected background and HAP-related characteristics were compared across the three study sites. Regular cooking was defined as cooking for at least a few times a week as in our previous studies ( Yu et al, 2018 , Chan et al, 2019a , Chan et al, 2019b ). A composite variable of cooking fuel combination was derived based on the types of fuels used for most meals (or all reported fuel types if none was noted as used for most meals).…”
Section: Methodsmentioning
confidence: 99%
“…Percentages and means of selected background and HAP-related characteristics were compared across the three study sites. Regular cooking was defined as cooking for at least a few times a week as in our previous studies ( Yu et al, 2018 , Chan et al, 2019a , Chan et al, 2019b ). A composite variable of cooking fuel combination was derived based on the types of fuels used for most meals (or all reported fuel types if none was noted as used for most meals).…”
Section: Methodsmentioning
confidence: 99%
“…Although the pulmonary and cardiac diseases have been the most studied adverse health, there are emerging evidence that air pollutants can damage any organ of the body and cause more ill-health. Chronic liver diseases [99], skin diseases [100], bone diseases [101] and autoimmune diseases [102] are increasingly been associated with air pollution. As data continues to increase on health effect of both HAP and AAP which are overlapping and contribute to each other, it is pertinent that all stakeholders; individuals, families, health care professionals, policy makers, governmental and non-governmental institutions work together to minimise the adverse health effects of the world's biggest environmental risk factor.…”
Section: Resultsmentioning
confidence: 99%
“…The point estimate of risk was lower in those who had switched from solid to clean fuels than long-term solid fuel users [OR]. Those who had ceased using solid fuels may get less exposed to solid fuel burning than longterm solid fuel users [duration in years: median (IQR): 16 (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) vs. 30 ]. Previous CKB study has demonstrated that the excess risk of all-cause mortality decreased by more than 60% in 5 years after cessation of indoor solid fuel burning (29).…”
Section: Discussionmentioning
confidence: 99%
“…Model 3 adjustment included all above variables and reproductive history (age at menopause, parity, contraceptive use) ( 15 ). We considered clean fuel group as our reference (defined as using gas and/or electricity in all recalled residences) ( 18 , 23 , 25 ). We also calculated the duration of solid fuel exposure during the recall period by summing the number of years at three residences where solid fuel (coal or wood) was reported as the primary cooking fuel.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation